2006
DOI: 10.1007/s11663-006-0065-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of the turbulent flow in induction furnaces

Abstract: Experimental results show that heat-and mass-transfer processes in recirculating turbulent flows, which comprise several vortexes of the mean flow, are significantly influenced by low-frequency large scale flow oscillations. The large eddy simulation (LES) model reproduces with good conformity not only these oscillations together with the dynamics of the macroscopic coherent structure, but also the turbulent energy transfer. Numerical studies, presented in this article, confirm the possibility of using LES for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
44
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 6 publications
3
44
0
2
Order By: Relevance
“…[6,7] The stirring processes and the melt flow in an ICF have been studied both numerically and experimentally for a long time. [8][9][10][11][12][13][14] Baake et al [8] demonstrated that the predictions, obtained with the standard k-e turbulence model are able to provide a good agreement with the experimentally determined time-averaged velocity field. However, the low-frequency pulsations in the velocity, which occur in the region between the main long-term vortices, prove difficult to be captured by adopting this model.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…[6,7] The stirring processes and the melt flow in an ICF have been studied both numerically and experimentally for a long time. [8][9][10][11][12][13][14] Baake et al [8] demonstrated that the predictions, obtained with the standard k-e turbulence model are able to provide a good agreement with the experimentally determined time-averaged velocity field. However, the low-frequency pulsations in the velocity, which occur in the region between the main long-term vortices, prove difficult to be captured by adopting this model.…”
Section: Introductionmentioning
confidence: 92%
“…The Large eddy simulation (LES) was found to be a good variant for more accurate predication of the low-frequency fluctuations and the temperature distribution in the melt. [9][10][11][12] Schwarze et al [14] performed an unsteady Reynolds averaged Navier-Stokes simulation (URANS) in order to investigate the turbulent melt flow in an ICF adopting the Reynolds stress turbulence model. Using this turbulence model, the predicted results showed the presence of the large flow structure with low frequency fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Due to a lot of force terms acting on inclusions, the motion of inclusions is very complex in the tundish with induction heating, which including floatation, adhesion to the wall, rotation, collision and coalescence. [11][12][13][14][15] Much effort has been devoted to understand the motion of inclusions with electromagnetic separation. [16][17][18][19][20][21] However, the temperature field was not taken into account in aforementioned works.…”
Section: Introductionmentioning
confidence: 99%
“…Typically two or more eddies with turbulent pulsations between them might form [1]. This phenomenon has been subject of various researches [2][3][4][5].Jardy et al[6] carried out experimental and theoretical study to characterize the hydrodynamic behavior and the transport of dissolved elements in the molten steel in vacuum induction furnace. 2D simulation using k-ε turbulence model, with a standard set of constants, showed adequate results [7,8].…”
mentioning
confidence: 99%
“…Nevertheless, in spite of the k-ε results demonstrating highest values of turbulent kinetic energy in the eddy centers and the lowest between the eddies, the experimental results showed that the maximum of the turbulent energy is between the vortices of the averaged flow and close to the wall of the crucible [5,9]. Umbrashko et al [5] simulated turbulent flow in an induction furnace for a low melting temperature metal and compared averaged with non-averaged Navier Stokes models. Their study revealed that the low-frequency velocity oscillations play the major role in the convective heat and mass transfer when flow structure contains two or more large vortexes of the mean flow.…”
mentioning
confidence: 99%